A COMPARATIVE ANALYSIS OF OPERATIONAL PRINCIPLES IN ISLAMIC AND CONVENTIONAL BANKING - Mehmood , Khalid; Lace , Natalja; Oganisjana , Karine (International Journal of Islamic Banking and Finance Research, 2025)
This article aims to explore & compare the operational principles of Islamic Banking (IB) & Conventional Banking (CB) to enhance awareness & deepen understanding of IB, with the further goal of establishing a foundation for the development of joint IB & CB products in Latvia. The study investigates a comparative analysis of IB & CB operational principles is conducted through a systematic literature review, highlighting key similarities & differences. Data was sourced from various electronic databases, with no restrictions on selecting papers based on the authors' religious backgrounds or countries of origin. The results show four key areas of similarity between IB & CB: both are financial institutions, operate globally, adhere to principles of corporate social responsibility, & are regulated by central banks. However, nine significant differences were observed concerning: the use of interest in capital allocation, profit & loss sharing mechanisms, regulatory frameworks, the influence of religious principles, conditions for current & savings accounts, investment opportunities & types, financing & insurance practices, security requirements, and late payment charges of funding. These findings help to underst the operational principles distinguishing IB from CB. This knowledge is valuable to researchers and potential clients of IB & CB to enhance their awareness & motivation to explore IB & CB products & services, and it enables them to make informed & flexible choices between the two banking systems based on their current needs, interests, & goals. The study also explores pathways for collaboration between the banking systems, proposing a customer-centric banking philosophy. JEL Classification Codes: E50, E58, G20, G21, G24, G29.